Traffic Monitoring and Analysis : 7th International Workshop, TMA 2015, Barcelona, Spain, April 21-24, 2015. Proceedings - Steiner, Moritz; Barlet-Ros, Pere.; Bonaventure, Olivier; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the thoroughly refereed proceedings of the 7th International Workshop on Traffic Monitoring and Analysis, TMA 2015, held in Barcelona, Spain, in April 2015. The 16 full papers presented in this volume were carefully reviewed and selected from 54 submissions. The contributions are organized in topical sections on measurement tools and methods; mobile and wireless; Web; security; and new protocols.
Measurement tools and methods -- Mobile and wireless -- Web -- Security.- New protocols.
Keywords: Computer Communication Networks; Computer system performance; Information storage and retrieva; Information Systems; Computer science; Computer Communication Networks; System Performance and Evaluation; Information Systems Applications (incl. Internet).; Information Storage and Retrieval; Management of Computing and Information Systems; Computers and Society